2014
DOI: 10.1007/s11147-014-9102-3
|View full text |Cite
|
Sign up to set email alerts
|

Are put-call ratios a substitute for short sales?

Abstract: Prior research argues that pessimistic traders can use options as substitutes for short sales particularly when stocks are expensive to short. Motivated by this contention, we examine the relation between put-call ratios, short-selling activity, and constraints to short selling. Results show that (1) put-call ratios are inversely related, instead of directly related, to proxies for short-sale constraints and (2) the significant negative relation between current put-call ratios and future returns (Pan and Potes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Huang et al (2019) show that there exists a substitution effect between short selling and options trading with respect to predicting aggregate stock returns. Nonetheless, Battalio and Schultz (2006), Blau andBrough (2015), andDeLisle et al (2016) suggest that a causal link between more active options trading and more short selling implies that they are complements to each other. Figlewski and Webb (1993) suggest that, while options trading plays a substitution role in mitigating the negative impact of short-sale constraints, and options trading and short sales are also complementary to each other for hedging purposes.…”
Section: Short-sale Effect Of Options On the Distortion Of Positive R...mentioning
confidence: 99%
“…Huang et al (2019) show that there exists a substitution effect between short selling and options trading with respect to predicting aggregate stock returns. Nonetheless, Battalio and Schultz (2006), Blau andBrough (2015), andDeLisle et al (2016) suggest that a causal link between more active options trading and more short selling implies that they are complements to each other. Figlewski and Webb (1993) suggest that, while options trading plays a substitution role in mitigating the negative impact of short-sale constraints, and options trading and short sales are also complementary to each other for hedging purposes.…”
Section: Short-sale Effect Of Options On the Distortion Of Positive R...mentioning
confidence: 99%
“…Billingsley and Chance (1988) found volume PCR as an effective forecasting tool in predicting the direction of the market. Blau and Brough (2015) in the US market found that current daily PCR of stock options is negatively related to next day's return, thus, as a contrarian trading strategy, PCR has the power of return predictability. Pan and Poteshman (2006) stated that the PCR constructed from buyer initiated volume (signed volume) contains information about future stock prices.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that first, mispricing is more likely to persist if limits to arbitrage are high, that is, if liquidity is low (see, for example, Lam and Wei 2011). Second, Blau and Brough (2015) argue that sophisticated investors especially prefer to trade in the option market if shorting in the stock market is constrained. In line with these arguments, we show that the previously documented phenomena tend to be stronger among stocks with high Amihud (2002) illiquidity, low institutional ownership, high bid-ask-spreads, and high option-implied volatility.…”
Section: Introductionmentioning
confidence: 99%